2021
DOI: 10.1101/2021.02.18.21251719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low somatosensory cortex excitability in the acute stage of low back pain causes chronic pain

Abstract: BACKGROUND: Determining the mechanistic causes of complex biopsychosocial health conditions such as low back pain (LBP) is challenging, and research is scarce. Cross-sectional studies demonstrate altered excitability and organisation of the primary somatosensory and primary motor cortex in people with acute and chronic LBP, however, no study has explored these mechanisms longitudinally or attempted to draw causal inferences. METHODS: Prospective, longitudinal, cohort study including 120 people with an acute e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…For example, in sub-acute LBP, greater functional connectivity of corticostriatal circuitry predicts chronic LBP at 1-year [8;72]. Further, using causal inference analyses, we have shown that low sensory cortex excitability (N80 SEP area) in acute LBP is a cause, and not an epiphenomenon, of chronic pain [50]. Our findings also demonstrate that BDNF genotype MET allele carriers are more susceptible to future LBP.…”
Section: Discussionsupporting
confidence: 55%
“…For example, in sub-acute LBP, greater functional connectivity of corticostriatal circuitry predicts chronic LBP at 1-year [8;72]. Further, using causal inference analyses, we have shown that low sensory cortex excitability (N80 SEP area) in acute LBP is a cause, and not an epiphenomenon, of chronic pain [50]. Our findings also demonstrate that BDNF genotype MET allele carriers are more susceptible to future LBP.…”
Section: Discussionsupporting
confidence: 55%
“…Measures recorded in the acute pain phase of LBP may also represent an epiphenomenon, but the reduced sensory-evoked potentials were demonstrated as causative of chronic pain after 6 months in contrast to the changes in the motor mapping. 105 Such data indicate that the cortical sensory-discriminative function is impaired in candidates vulnerable to developing chronic musculoskeletal pain. How this links with the sensory-discriminative function in painful stimulations is unknown, although previous studies demonstrated augmented nociceptive-evoked potentials (short latency) in patients with chronic LBP 49 and fibromyalgia 50 compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to supraspinal mechanisms, growing evidence suggests that chronic low back pain (CLBP) is linked to neuroplastic adaptations of the brain (Flor et al, 1997, Ung et al, 2014, Rodriguez-Raecke et al, 2014, Konno and Sekiguchi, 2018). Thus, in light of its potential clinical relevance, neural reorganization, specifically in the primary somatosensory and in the motor cortices, has been studied with growing interest in back pain contexts (Flor et al, 1997, Flor, 2003, Tsao et al, 2010, Van DieĂ«n et al, 2017, Zhang et al, 2019, Jenkins et al, 2022, Moseley and Flor, 2012).…”
Section: Introductionmentioning
confidence: 99%